Death in Krčmar: A Contribution to the Quantification of the Victims of the 1918 Spanish Flu Pandemic - Vladimir Krivošejev (University of Belgrade, 2020)
It is estimated that the Spanish flu pandemic, which affected the entire planet from 1918 to 1919, affected about five hundred million people, or one-third of the world's population at the time, and killed about fifty million people. The disease was noticed among Serbian soldiers in Corfu in April 1918, and in May among soldiers on the Salonika Front, but without fatal consequences. During the summer, fatalities were also reported, mainly due to lung compaction. Then the epidemic was reported in occupied Serbia as well.